Analysis of Marketing Strategies in Increasing Sales at Lilis Grosir in Palopo City - Esse*, Esse; Addriani, Fika; Nurjannah, Nurjannah; Mahmut, Cici (Universitas Syiah Kuala, 2024)
In an increasingly competitive business world, marketing strategies play a crucial role in determining a company's success or failure. This research aims to analyze marketing strategies to increase sales at Lilis Grosir in Palopo City. Data for this study was obtained through two methods: Field Research and Library Research. The collected data includes quantitative data, such as sales figures and costs, and qualitative data obtained from interviews. The data sources include primary data, directly obtained from the company, and secondary data, sourced from related documents and books. The data analysis process involves three stages: data collection, which classifies internal and external data; analysis using the SWOT Matrix; and decision-making based on the analysis results. Based on internal and external analysis, Lilis Grosir's main strategy is a growth strategy, where the company can develop its retailers and stores by enhancing resource capabilities and utilizing better promotions. This strategy is appropriate for increasing sales. According to the SWOT Matrix, growth through the store's internal and external factors can benefit the store's advancement. Lilis Grosir's marketing strategy should increase promotional activities by utilizing social media to share beauty tips, ensuring the message reaches a wider audience and, consequently, increasing sales.